(untitled) (Revista de Ciências Agroveterinárias, 2015)
The study aimed to determine the technological properties of cement-wood panels produced with the particle Eucalyptus benthamii Maiden et Cambage. The experiment plan consisted of four compositions with different treatments of the particles (cold water, hot water, sodium hidroxyde (NaOH) and calcium hidroxyde (Ca(OH)2), and a control composition. The panels were produced with nominal specific gravity of 1.20 g cm-³, with the ratios wood:concrete 1:2.75 and water:cement 0.40. The panels were evaluated for their physical and mechanical properties through the European standard EN. Analyses were performed to verify the occurrence of outliers, data normality and homogeneity of variances, and subsequently submitted to analysis of variance and Tukey test. The results of physical and mechanical properties of the panels indicated that the best method of treating particles is through the use of Ca(OH)2. With the exception of the modulus of rupture, the thickness swelling, modulus of elasticity and tensile perpendicular, they met the specifications of commercial panels produced by the BISON process. Therefore, the feasibility of use of Eucalyptus benthamii for wood-cement panels production was discovered.